Soil Quality Evaluation of Inceptisol Based on the Alberta Card (Case Study of Horticultural Land in Titi Papan, Medan Deli District) - Kemala Sari; Mukhlis (Jurnal Online Pertanian Tropik, 2025)
Soil quality describes the suitability of the physical, chemical, and biological properties of soil that together function as a medium for plant growth. The Alberta Soil Quality Card is one method for evaluating soil quality through soil quality indicators, such as organic matter content, drainage, water-holding capacity, soil microorganisms, and erosion. This research was conducted to evaluate the Inceptisols soil quality of horticulture land in Titi Papan, Medan Deli District, based on the indicators listed in the Alberta Soil Quality Card to obtain appropriate soil management recommendations based on the evaluation results. The results of soil quality observation in the horticultural land of Titi Papan, Medan Deli District, indicate that the preferred score (P) is found in the indicators of plant/weed strength, nurseries, soil fertility, and salinity. A medium score (M) is obtained in the indicators of residue cover, organic material color, drainage/infiltration, aggregation, and soil life, including the presence of worms, compaction/rooting, and water erosion. The limiting factor with a low score (L) is obtained in the indicator of water holding capacity.